THE DISCRETE EVENT SIMULATIONS EFFECT ON COURIER LOGISTICS DIGITIALIZATIONS AND ITS CONTRIBUTIONS TO INDUSTRY 4.0 WITHIN THE RESILIANCE ECONOMY: A QUANTITATIVE STRATEGY - Hanafi Ahmad; Fadly Habidin; Azman Hasan; Siti Norida Wahab (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
The swift digital transformation of courier logistics is transforming the sector, propelled by the imperatives of Industry 4.0 and the necessity for resilience in the changing global economy. This article examines the influence of Discrete Event Simulation (DES) on the digital transformation of courier logistics and its role in Industry 4.0 frameworks within the context of a resilient economy. Discrete Event Simulation (DES) functions as an effective instrument for modelling and optimising intricate logistical systems, allowing organisations to improve operational efficiency, adaptability, and sustainability. This research employs a quantitative case study methodology to analyse how DES applications tackle significant issues, including real-time decision-making, resource allocation, and supply chain disruptions. The findings highlight the crucial importance of DES in promoting digital innovation, enhancing system resilience, and facilitating the incorporation of Industry 4.0 technologies in courier logistics. This research underscores the revolutionary capacity of DES as a catalyst for attaining a robust, sustainable, and digitally optimised logistics sector.